Assessment of exercise-associated gastrointestinal perturbations in research and practical settings: methodological concerns and recommendations for best practice - Costa, R. J.; Young, P.; Gill, S. K.; Snipe, R. M.; Gaskell, S.; Russo, I.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Strenuous exercise is synonymous with disturbing gastrointestinal integrity and function, subsequently prompting systemic immune responses and exercise-associated gastrointestinal symptoms, a condition established as "exercise-induced gastrointestinal syndrome." When exercise stress and aligned exacerbation factors (i.e., extrinsic and intrinsic) are of substantial magnitude, these exercise-associated gastrointestinal perturbations can cause performance decrements and health implications of clinical significance. This potentially explains the exponential growth in exploratory, mechanistic, and interventional research in exercise gastroenterology to understand, accurately measure and interpret, and prevent or attenuate the performance debilitating and health consequences of exercise-induced gastrointestinal syndrome. Considering the recent advancement in exercise gastroenterology research, it has been highlighted that published literature in the area is consistently affected by substantial experimental limitations that may affect the accuracy of translating study outcomes into practical application/s and/or design of future research. This perspective methodological review attempts to highlight these concerns and provides guidance to improve the validity, reliability, and robustness of the next generation of exercise gastroenterology research. These methodological concerns include participant screening and description, exertional and exertional heat stress load, dietary control, hydration status, food and fluid provisions, circadian variation, biological sex differences, comprehensive assessment of established markers of exercise-induced gastrointestinal syndrome, validity of gastrointestinal symptoms assessment tool, and data reporting and presentation. Standardized experimental procedures are needed for the accurate interpretation of research findings, avoiding misinterpreted (e.g., pathological relevance of response magnitude) and overstated conclusions (e.g., clinical and practical relevance of intervention research outcomes), which will support more accurate translation into safe practice guidelines.